Metal-Ion-Intercalated MXene Nanosheet Films for NH3Gas Detection - Kim, S.; Lee, J.; Doo, S.; Kang, Y.C.; Koo, Chong Min; Kim, S.J. (American Chemical Society, 2021)
High conductivity and transparency and sheet-like two-dimensional morphology of MXenes make them attractive for use as functional transparent thin films. In addition, because of the dense surface functional groups and negative surface charge of the MXene sheet, cationic species can be easily intercalated into MXene interlayers to largely enhance the film properties and device performance. In this paper, for the first time, we demonstrate a spontaneous self-assembly method to efficiently intercalate metal ions into MXene transparent thin films with cation-dependent properties. Unlike in previous methods that intercalate ions after film assembly, monovalent and divalent metal ions are easily intercalated during the self-assembly process within a very short period of time. The optoelectronic properties are dependent on the intercalated cation where uniformly assembled ion-intercalated Ti3C2Tx MXene thin films exhibited on average a high optical transmittance of ∼90% at a wavelength of 550 nm. The ion-intercalated MXene films were utilized as gas sensors to detect ammonia gas. Interestingly, metal-ion-intercalated films showed a much higher signal-to-noise ratio upon exposure to ammonia gas compared to that of films assembled without metal ions, demonstrating the positive influence of metal-ion intercalation on enhancing the gas-sensing performance. ？ 2021 American Chemical Society.